2004
DOI: 10.1037/0893-3200.18.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Problems of Children Living With Drug-Abusing Fathers: Comparisons With Children Living With Alcohol-Abusing and Non-Substance-Abusing Fathers.

Abstract: Although the effects of paternal alcoholism on the psychosocial adjustment of children are well documented, the impact of fathers' illicit drug abuse on their children is poorly understood. The purpose of this study was to compare the adjustment of children living in families with drug-abusing fathers (n = 40) with that of children with fathers who abused alcohol (n = 40) and children with non-substance-abusing fathers (n = 40). Children with drug-abusing fathers experienced more internalizing and externalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 47 publications
(50 reference statements)
3
79
1
1
Order By: Relevance
“…In the Illinois study, 43% of children did not have significant problems per foster parent report. Similarly, other studies of children of parents who abuse alcohol and other substances while reporting elevated levels of mental health problems also demonstrate individual variations in outcomes (Fals-Stewart, Kelley, Fincham, Golden, & Logsdon, 2004). These findings raise questions about protective factors that might explain the variations in the mental health outcomes of children who experience parental substance abuse.…”
Section: Introductionmentioning
confidence: 95%
“…In the Illinois study, 43% of children did not have significant problems per foster parent report. Similarly, other studies of children of parents who abuse alcohol and other substances while reporting elevated levels of mental health problems also demonstrate individual variations in outcomes (Fals-Stewart, Kelley, Fincham, Golden, & Logsdon, 2004). These findings raise questions about protective factors that might explain the variations in the mental health outcomes of children who experience parental substance abuse.…”
Section: Introductionmentioning
confidence: 95%
“…Research further suggested that parents who are substance-involved exhibit different parenting behaviors than those who are not substance-involved, with such differences varying with the characteristics of parents' current drug use (see (20) and (21) for reviews). For example, parents who are substance-involved are more likely to exhibit greater parenting stress (22), decreased attentiveness and engagement with their children (23), more authoritarian parenting (24), and dysfunctional or harsh disciplinary practices (25). Given such parenting practices, it should not be a surprise that children of these parents are three times more likely to be abused and four times more likely to be neglected relative to children of parents who are not substance-involved (26).…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%
“…Recent studies have shown that 20% to 47% of parents entering treatment for substance abuse live with a child (e.g., Collins et al, 2003;Fals-Stewart et al, 2004a;Stanger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these children appear at elevated risk for depression and anxiety (Fals-Stewart et al, 2004a;Stanger et al, 1999), poor self-concept (Drucker and Greco-Vigorito, 2002), externalizing problems (Kelley and Fals-Stewart, 2004), academic difficulties (e.g., Blanchard…”
Section: Introductionmentioning
confidence: 99%